'Something more than one phase of treatment': Sunaya, an adopted adolescent patient who asked to return to therapy. Issue 2 (4th May 2022) - Mirvis, Hillel
ABSTRACT: This paper discusses my work with Sunaya, an adopted adolescent girl who asked to return for a second phase of therapy. This happened several months after her first phase of treatment had abruptly been brought to an end, due to unsolicited organisational changes. Sunaya's search for identity was severely compromised by her having been abandoned at birth by her biological parents to a foreign orphanage, and subsequently being adopted at five months of age. In this second phase of therapy, I was struck by the extent to which Sunaya was now so suddenly driven to make sense of her origins in open discussion, managing to process and integrate the biological and adopted parts of herself in a way which had not seemed possible in our earlier work. This enabled her to make considered decisions about the next stages of her life post 18. I suggest that the original ending of Sunaya's therapy, followed by our therapeutic reunion, represented in her mind a reunion with her biological parents; within the therapy Sunaya's curiosity and ambivalence about such a reunion could be safely worked through. I link Sunaya's request for 'something more' than one phase of treatment with Stern's ideas about offering 'something more' to some of the most deprived patients in therapy. I further suggest that Henry's ideas about some fostered and adopted children being 'doubly deprived' helped me understand Sunaya's need for a 'double dose' of therapy, in order to redress how she had internalised multiple experiences of deprivation. This further helps us understand the need for looked after children to develop stronger attachments in multiple contexts.